Posaconazole-Loaded PVA/SA-L-Valine Composite for Sustained Drug Delivery with Docking Study - Naveenkumar, Ramachandiran; Nithiyasri, Parameswari Ravichandran; Karthikeyan, Balakrishnan (Sustainable Chemical Engineering, 2026)
Self-Assembled L-valine (SA-L-valine) was synthesized and Posaconazole (POS)-Loaded Polyvinyl Alcohol (PVA) with SA-L-valine composite films were fabricated using a solvent evaporation method. The prepared samples were characterized by Fourier-Transform Infrared Spectroscopy (FT-IR), X-Ray Diffraction (XRD), and Field-Emission Scanning Electron Microscopy (FE-SEM). XRD results confirmed that SA-L-valine was properly incorporated into the POS/PVA matrix, forming an ordered morphology. FT-IR spectra revealed strong intermolecular interactions, suggesting effective complex formation, and FE-SEM images showed a clear sheet-like surface morphology with uniform structural organization. The drug release study at pH 3.4, 5.5, and 7.4 showed cumulative releases of 96.01%, 98.23%, and 95.52% within 24 h, respectively. The highest release at pH 5.5, which corresponds to the natural skin surface pH, indicates that the PVA/SA-L-valine film loaded with posaconazole is suitable for topical antifungal applications. In vitro antifungal activity evaluation using the disk diffusion method demonstrated significant inhibitory effects against fungal pathogens. Furthermore, molecular docking studies with the lipid transfer protein Sec14p from Saccharomyces cerevisiae demonstrated favorable binding interactions, confirming that the drug maintained its biological activity after formulation. These findings suggest that this composite may be a promising sustained release antifungal drug delivery system.